Effect of Type and Concentration of Encapsulating Agents on Physicochemical, Phytochemical, and Antioxidant Properties of Red Dragon Fruit Kombucha Powdered Beverage - Rena Agatha; Yati Maryati; Agustine Susilowati; Aspiyanto Aspiyanto; Anastasia Fitria Devi; Hani Mulyani; Setyani Budiari; Euis Filailla; Della Rahmawati; Nina Artanti (Research Center for Chemistry - LIPI, 2021)
Kombucha is a healthy beverage from the fermentation of sugared tea with a symbiotic culture of bacteria and yeast (SCOBY). There is a growing interest on kombucha due to the reported health benefits. The original kombucha is prepared using only sweetened black tea infusion. The development of kombucha, however, has been reported to incorporate other plant water extracts. A previous study showed that kombucha beverage using red dragon fruit (RDF) as an alternative substrate gave the highest antioxidant activity at 15 days of fermentation. RDF kombucha instant powder could be a new food product development due to its longer shelf life, convenience, and low distribution cost. This study aimed to determine the best and the concentration of encapsulating agent for RDF kombucha powdered beverage which could retain the antioxidant properties. RDF kombucha was spray dried using maltodextrin, gum arabic, and inulin as the encapsulating agents with various concentrations (5%, 10%, and 15%). Gum arabic was the best encapsulating agent since it gave the highest values of drying yield, pH, and total phenolic content retention, in comparison to the other two encapsulating agents. Within the observed concentrations, the incorporation of gum arabic resulted in RDF kombucha powder with a similar appearance, red colour, and antioxidant retention. Thus, the 5% addition of gum arabic is recommended for future preparations of RDF kombucha powdered beverage.